The Effect of LDR, NPL, CAR on Return on Asset of Conventional National Commercial Bank in Indonesia - Sochib Sochib (International Journal of Accounting and Management Research, 2023)
Every effort to increase company profits impacts the prosperity of investors as owners. Profit optimization involves aligning assets, particularly in banking, where key factors influencing profits include the bank's ability to allocate funds as credit and the management's proficiency in handling loans to maintain collectibility and ensure sufficient capital. Loan distribution is measured using the Loan to Deposit Ratio (LDR), while effective credit management is gauged by Non-Performance Loans (NPL). The adequacy of minimum capital provision is assessed by the Capital Adequacy Ratio (CAR). This study aims to demonstrate the influence of LDR, NPL, and CAR on Return on Assets (ROA) during the 2017-2021 period in Indonesian national commercial banks. Purposive sampling selects a representative sample, and linear regression is employed to analyze the variables' impact. The research findings indicate that LDR and NPL have a significant effect on ROA, while CAR does not.